INTEGRATION OF SUSTAINABLE DEVELOPMENT PRINCIPLES INTO PUBLIC ADMINISTRATION - Ogorodniichuk, Mariia (Public Management and Policy, 2025)
This essay examines the theoretical foundations, worldwide practices, and internal traits of integrating sustainable development principles into Ukraine’s public administration framework, as well as the possibilities for their real-world implementation. The importance of the study arises from the growing need to move toward sustainable progress as a global demand, the disparity between the domestic public administration system and current socio-economic and ecological problems, and also the need to develop effective approaches for integrating economic, social. The objective is to confirm the theoretical foundations and develop practical guidance on incorporating the principles of sustainable development into Ukraine’s public administration, taking into account global expertise, national characteristics, and contemporary challenges. The key is to establish effective mechanisms and instruments for embedding sustainable development principles in public administration, ensuring a balance of financial, social, and ecological priorities, and enhancing the efficacy of state policy amidst modern national and global challenges. The piece analyzes the theoretical and methodological bases of the notion of sustainable development and its progression within the global setting. The core tenets of sustainable development and methods for their incorporation into the system of state and municipal governance are identified. The status and prospects for integrating the principles of sustainable development into Ukraine’s public administration are studied. The worldwide practice of including sustainable development principles in public administration is described. The primary challenges, hindrances, and dangers to incorporating sustainable development principles into Ukraine's public administration are pinpointed. Considering worldwide experience and Ukrainian conditions, a “roadmap” for implementing sustainable development into Ukraine's public administration has been created. Additional study should concentrate on developing complete frameworks for integrating sustainable advancement into public governance, improving the method for observing and evaluating the effectiveness of these incorporations.